2010
DOI: 10.1007/s12185-010-0546-4
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon case of chronic myeloid leukemia with multiple myeloma

Abstract: We describe a 72-year-old woman who was diagnosed with asymptomatic multiple myeloma (MM) while being treated for Philadelphia (Ph)-positive chronic myeloid leukemia (CML) with imatinib mesylate (400 mg/day). The diagnosis of CML was based on the presence of the Ph chromosome and chimeric BCR-ABL messenger RNA. Three months after starting imatinib mesylate treatment, the patient achieved a complete cytogenetic response. However, bone marrow analysis at that time demonstrated plasmacytosis, and paraprotein (IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 23 publications
0
30
0
3
Order By: Relevance
“…There have also been scattered reports of coexistence of CML with other lymphoid malignancies such as CLL 28,29 and multiple myeloma. 30 In our analysis, the overall SIR of second cancers was 0.60 (95% CI, 0.44-0.81), suggesting a lower than expected rate of malignancies in patients treated with TKI, although the incidences of melanoma, endocrine tumors, kidney cancers, and CLL were higher than expected. Our results are in contrast to the observations by Roy et al of an unexpected increase in cancers among patients treated with imatinib mesylate.…”
Section: Discussionmentioning
confidence: 45%
“…There have also been scattered reports of coexistence of CML with other lymphoid malignancies such as CLL 28,29 and multiple myeloma. 30 In our analysis, the overall SIR of second cancers was 0.60 (95% CI, 0.44-0.81), suggesting a lower than expected rate of malignancies in patients treated with TKI, although the incidences of melanoma, endocrine tumors, kidney cancers, and CLL were higher than expected. Our results are in contrast to the observations by Roy et al of an unexpected increase in cancers among patients treated with imatinib mesylate.…”
Section: Discussionmentioning
confidence: 45%
“…The transformation to lymphoid cell in the blastic phase of CML has suggested the existence of a common stem cell, capable of differentiating into both myeloid and lymphoid cells. The common stem cell hypothesis has not been demonstrated in the rare case reports [5] . However, Breitkopf et al [10] studied H929 and other MM cell lines in search of kinase signaling pathways which could be inhibited by the recently developed TKIs.…”
Section: Discussion and Literature Reviewmentioning
confidence: 96%
“…One disease usually precedes the other, but concurrent diagnosis of both has also been reported. Ide et al [5] reported a case of an elderly woman who developed IgGκ MM only 3 months after starting treatment on imatinib. Klenn et al…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The coexistence of chronic myeloid leukemia (CML) and multiple myeloma (MM) in the same patient has rarely appeared in the literature [1][2][3][4][5][6][7][8][9]. Furthermore, the simultaneous diagnosis of these two diseases is very rare in previous case reports [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the simultaneous diagnosis of these two diseases is very rare in previous case reports [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%